Sustainable Development Dimensions and Urban Agglomeration - Battisti, Alessandra; Baiani, Serena (IntechOpen, 2022)
Due to climatic, social, and epidemiological challenges, urban areas are suffering from recurring problems that require profound and sustainable solutions. Although they cover only a small area of the earth's surface, metropolises are responsible for most of the world's global carbon emissions, which cause adverse effects on energy and the climate. This book discusses the spatial development of urban areas in the context of the United Nations Sustainable Development Goals. Chapters address the problems of large urban agglomerations, examine their impacts on both people and the environment, and propose intervention policies and strategies. The book also presents case studies from different areas of the world, including Chile, Brazil, and India.